2020
DOI: 10.1002/jpln.202000099
|View full text |Cite
|
Sign up to set email alerts
|

Iodine uptake and translocation in apple trees grown under protected cultivation

Abstract: Background and Aims: Agronomic biofortification of food crops with iodine may improve the dietary intake of this trace element, which is essential for human development and health. So far, little is known about the suitability of this technique in pome fruits. The objectives of this study were (1) to investigate uptake and translocation of exogenously applied iodine in apple trees, (2) to identify possible strategies of iodine biofortification for this type of fruit, and (3) to evaluate interactions between fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
7
17
0
Order By: Relevance
“…Similarly, also I and Se seem to be not antagonistic ( Table 6 ). Also in previous studies, no clear interaction was found between I and Se during their leaf absorption and transportation to wheat grains ( Zou et al, 2019 ), lettuce roots ( Smoleń et al, 2014 ), kohlrabi tubers ( Golob et al, 2020 ) and apple fruits ( Budke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, also I and Se seem to be not antagonistic ( Table 6 ). Also in previous studies, no clear interaction was found between I and Se during their leaf absorption and transportation to wheat grains ( Zou et al, 2019 ), lettuce roots ( Smoleń et al, 2014 ), kohlrabi tubers ( Golob et al, 2020 ) and apple fruits ( Budke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 85%
“…Similar findings related to phloem transportation of I have been also reported by Smoleń et al (2016) and Landini et al (2011) . By contrast, there are studies showing poor phloem transport of I in the plants such as in young spinach plants ( Humphrey et al, 2019 ) and apple trees ( Budke et al, 2020 ). In case of the studies with apple trees, the increases in I concentration of the fruits, which were kept in plastic bags during the foliar spray, were around 4- to 5-fold compared to the trees without foliar I spray (i.e., from 0.4 μg up to 2.0 μg per 100 g FW) ( Budke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important because a previous study on apples showed that more than half of the foliar-sprayed I is localized in the fruit peel. Nevertheless, I in the peel is hardly affected by washing of the fruit under running water – this reduced the fruit I content by only 8% ( Budke et al, 2020a ). Thus, when fresh pome fruits are consumed, most of the biofortified I usually becomes nutritionally effective.…”
Section: Introductionmentioning
confidence: 99%